ANALYSIS OF CONDITIONS OF DETENTION OF WOMEN IN PLACES OF IMPRISONMENT: NATIONAL LEGISLATION, INTERNATIONAL STANDARDS AND PRACTICAL RECOMMENDATIONS - Kazbayeva , Асель Габиденовна (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2025)
The article presents a comprehensive analysis of the legislation of the Republic of Kazakhstan regulating the conditions of detention for women in places of deprivation of liberty, including women with minor children. The author examines the degree of compliance of national legal acts with international standards, including the United Nations Standard Minimum Rules for the Treatment of Prisoners (Nelson Mandela Rules), the Bangkok Rules, and the Convention on the Elimination of All Forms of Discrimination against Women (CEDAW). The Penal Execution Code of the Republic of Kazakhstan provides for special conditions of detention: enhanced food rations, access to medical care, adapted living conditions, and social support measures. However, monitoring results show that these guarantees are only partially implemented in practice. Correctional facilities face limited funding, a shortage of qualified personnel, and poor sanitary conditions. These issues are particularly acute for pregnant women and mothers with children. There is also serious concern regarding the limited access to mechanisms of parole and the replacement of sentences with more lenient forms. Although such measures are provided for in Articles 72 and 73 of the Criminal Code of the Republic of Kazakhstan, their application is hindered by the mandatory requirement of full compensation for material damage. For women without financial support, this requirement becomes an insurmountable barrier, depriving them of a real chance at early release. Thus, despite the existence of formal legal guarantees, their practical implementation with respect to women requires systemic improvement. Enhancing the effectiveness of law enforcement, improving detention conditions, and eliminating social barriers are key steps toward aligning national practices with international standards.